Synoptic time-scale variability of sediment temperature profile and sound speed in shallow seas derived from in situ observations. (5th October 2020) - Yang, Guang-Bing; Zheng, Quanan; Hu, Xiaomin; Ma, De-Jing; Chen, Zhao; Yu, Long; Ju, Xia; Zhuang, Zhanpeng; Hui, Zhenli; Guo, Yan-Liang; Sun, Jia; Chen, Liang; et al.
Abstract: In this study, to investigate the synoptic time-scale variability of sediment temperature profile and sound speed in shallow seas, one-month-long in situ observations were conducted in Jiaozhou Bay using a newly designed sediment measurement system. A typhoon passage and a heavy rainfall process were captured during the observation. The sediment temperature increased immediately after the significant bottom water temperature increase induced by typhoon passage. A significant increase in the sediment warming rate could be identified at a depth as deep as 0.8 m below seafloor (mbs), and a significant increase in downward sediment heat flux at 0.5 mbs lasted until five days after the typhoon passed. The sediment sound speed was also observed to decrease or increase as soon as the bottom water salinity significantly decreased or the bottom water temperature significantly increased. Moreover, the pore water salinity—which can affect the sediment sound speed—cannot be conducted like heat but can be changed only by diffusion or convection processes, and the static diffusion of salt was too slow for the observed sediment sound speed variation; we therefore conclude that in addition to heat conduction, the pore water convection may play an important role in the synoptic time-scale variations of the sediment temperature and sound speed, which is also consistent with the simulation results. Highlights: Synoptic time-scale variability of sediment is derived from in situ observations. Sediment temperature profile and sound speed respond quickly to weather process. Both heat conduct and pore water convection contribute to synoptic sediment variation.